Literature Review : The Role of Polyphenols in Modulating Gut Microbiota and Their Anti-Inflammatory Effects on Inflammatory Bowel Disease (IBD) - Rahmah, Rifka Annisa; Mahmudiono, Trias (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Inflammatory Bowel Disease (IBD) is an idiopathic condition characterized by chronic inflammation of the digestive tract. The prevalence of IBD in Southeast Asia has increased from 103,000 cases in 2017 to approximately 118,000 cases in 2020. Diet plays a crucial role in the development and progression of IBD. Polyphenols, bioactive compounds in plant-based foods, interact with molecular targets to inhibit inflammation and protect against oxidative stress. Additionally, polyphenols modulate the gut microbiota, promoting the growth of beneficial bacteria. Objectives: The study aimed to review the effects of polyphenols from various food sources in reducing inflammation and enhancing gut microbiota diversity as a potential therapeutic approach for IBD. Methods: This study used a literature review method, analyzing experimental in vivo studies. Data were collected by searching for published articles in ScienceDirect, Google Scholar, and PubMed. Results: Eight studies were identified discussing the role of polyphenols in IBD. Polyphenols from various sources, including camellia oil, EGCG from green tea, resveratrol, kiwi polyphenol extract, curcumin, luteolin, bee pollen, and flavonoids, were found to have positive effects on modulating gut microbiota composition and reducing inflammation in animal models of IBD. Conclusions: Polyphenols have potential as a therapeutic agent for IBD by inhibiting inflammation and promoting gut microbiota diversity.